Teacher Leader Competency in Implementing Merdeka Curriculum: A Case Study at SD Negeri 212 Palembang - Wati, Ariesta Dwi Indah Kusuma; Arafat, Yasir; Mahasir, Mahasir (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The purpose of this research is to analyze the abilities of the teaching staff in order to increase student confidence in the implementation of the Merdeka Curriculum at Sekolah Dasar Negeri 212 Palembang. One of the key factors in ensuring the success of curriculum implementation is the teacher’s ability to make learning more flexible, creative, and engaging for students. The method of research that is used is a qualitative approach using data collection techniques such as observation, documentation, and interviews. The study’s findings indicate that a teacher’s pedagogical, professional, social, and personal competencies significantly contribute to the improvement of the quality of the teaching process and the learning outcomes of the students. In addition, the active teacher in implementing the Merdeka curriculum can create innovative and flexible learning environments that meet the needs of students. This study recommends teachers increase their students’ learning and development so that their skills continuously improve when learning a new curriculum.